2022
DOI: 10.1029/2022je007523
|View full text |Cite
|
Sign up to set email alerts
|

Winds at the Mars 2020 Landing Site. 2. Wind Variability and Turbulence

Abstract: Variability in surface winds is a key element in aeolian studies. Two mechanisms dominate the dust lifting on Mars: surface wind stress lifting and convective vortex lifting. Outside convective vortices, dust is lifted when the surface wind stress exceeds a threshold value, and sand particles are then moved by drag forces and bounce along the surface, in a process known as saltation (e.g., Petrosyan et al., 2011). Saltation responds to changes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…The InSight pressure data demonstrated a shallower slope that expected for the inertial regime (Banfield et al, 2020;Temel et al, 2022). For Perseverance at Jezero, Viúdez-Moreiras, Torre, et al (2022) 2022) showed steeper slopes (−2.6 and −1.9 between 0.1 and 1 Hz) for temperature. Of particular note, on Mars the dissipative regime begins at lower frequencies than on Earth.…”
Section: The Martian Planetary Boundary Layermentioning
confidence: 80%
See 1 more Smart Citation
“…The InSight pressure data demonstrated a shallower slope that expected for the inertial regime (Banfield et al, 2020;Temel et al, 2022). For Perseverance at Jezero, Viúdez-Moreiras, Torre, et al (2022) 2022) showed steeper slopes (−2.6 and −1.9 between 0.1 and 1 Hz) for temperature. Of particular note, on Mars the dissipative regime begins at lower frequencies than on Earth.…”
Section: The Martian Planetary Boundary Layermentioning
confidence: 80%
“…The Perseverance wind speeds were collected on a 1 hr on 1 hr off cadence and can be up to 2 Hz. Viúdez-Moreiras, Lemmon, et al (2022);Viúdez-Moreiras, Torre, et al (2022) have demonstrated that the winds at Jezero are generally calmer than other landing sites but have a slightly higher turbulent intensity than at InSight. However, several boards of the Perseverance wind sensor were damaged (Lemmon et al, 2022;Viúdez-Moreiras, Lemmon, et al, 2022) due to wind-induced sand particle impacts especially during a regional dust storm on sols 313 and 315 (Hueso et al, 2022b), thus hindering the wind retrieval with the same accuracy.…”
Section: The Martian Planetary Boundary Layermentioning
confidence: 98%
“…A close encounter with a dust devil (DD) on sol 313 at 13:42 hr local true solar time (LTST) further damaged WS2 (see the companion paper, Viúdez‐Moreiras et al. (2022), hereafter referred to as part 2). Two sols later (sol 315 at 14:24 hr LTST), the damage was produced on WS1 and the MEDA WS was unavailable to provide wind data, leaving only three operative sensor boards: one on WS2 and two on WS1.…”
Section: Methods: the Mars 2020 Meda Wind Sensor And Observationsmentioning
confidence: 99%
“…Data from both booms are combined to produce horizontal wind speed and direction values of the highest confidence, with accuracies of ±1 m/s and a resolution of 0.5 m/s for wind speeds <10 m/s, and 10% of the measurement and 0.1 m/s for wind speeds between 10 and 40 m/s. The WS was damaged by a dust devil during the regional dust storm around sols 312–318 (Ls 152°–156°) (Hueso et al., 2022; Lemmon et al., 2022; Viúdez‐Moreiras, de la Torre, et al., 2022; Viúdez‐Moreiras, Lemmon, et al., 2022). Thus, WS measurements of the highest confidence are only available for the first 313 sols of the mission (Figure S1 in Supporting Information ).…”
Section: The Meda Instrumentmentioning
confidence: 99%